The Plotting Check of Land Parcels on Computerization of Land Activities (KKP) towards Complete Village in Medan City - Ramadhani, Rahma; Ningrum, Fatimaharani Annisa Septiya; Delly Rasendria, Alysia (BHUMI: Jurnal Agraria dan Pertanahan, 2025)
Abstract: The Plotting check serves as a strategic solution to address land-related issues where parcels are registered but remain unmapped due to the transition from analog to digital data systems. This necessitates the synchronization of both spatial and textual data through the implementation of KKP-Web and AutoCAD GeoKKP applications. This process is in alignment with the Ministry of Agrarian Affairs and Spatial Planning / National Land Agency's objectives to enhance electronic services. This research aims to map all land parcels within the Sitirejo II subdistrict as a decision-support tool for resolving land management challenges. The ultimate goal is to establish a harmonious integration between administrative functions, policy frameworks, and land information infrastructure, thereby contributing to the realization of sustainable development. The study employs a mixed-methods approach, combining quantitative techniques utilizing secondary data and spatial analysis, alongside qualitative methods through interviews. The analysis involves overlaying all registered land parcels onto the national coordinate system and validating land parcels, survey documents (SU), and land books (BT) using the KKP-Web application. The findings of this research resulted in a comprehensive land map of Sitirejo II, covering a total of 1,317 parcels, categorized into two distinct groups: (i) 1,013 parcels with complete data sets, including parcel details, SU, and BT, and (ii) 304 parcels with incomplete or missing data on parcels, SU, and BT. In conclusion, the plot-checking initiative for the Medan Land Office significantly enhances the quality of both spatial and textual land data, facilitating informed decision-making and policy development, and supporting the orderly management of land administration. Keywords: Data Quality, Land Parcel, Plotting Check, Validation